The Letters to Philemon, the Colossians, and the Ephesians: A Socio-Rhetorical Commentary on the Captivity Epistles - Bernas, Casimir (Cistercian studies quarterly, 2009)
The article reviews the book "The Letters to Philemon, the Colossians and the Ephesians: A Socio-Rhetorical Commentary on the Captivity Epistles," by Ben Witherington.